Osteologic development of the viscerocranial skeleton in sea bream A lternative ossification strategies in teleost fish - Faustino, M. (2014)
The ontogeny of the viscerocranial skeleton of sea bream Sparus aurata larvae was studied from 1 to 90 days post-hatching. In the smallest specimens analysed at 2·7 mm LN no cephalic elements were present and at 3·1 mm LN the following cartilaginous structures were visible: trabecula cranii, auditory capsule, Meckel’s cartilage, quadrate, hyosymplectic cartilage, sclerotic, hypohyal, ceratohyal epihyal cartilage, interhyal, hypobranchial 1 and ceratobranchial 1. The only structure ossified at this size is the maxillary and the next ossified structures to appear are the preopercle and opercle at about 3·7 mm LN. The last bones to appear are infraorbital 2 and 6 at 15·1 mm LS. The first cartilaginous elements and structures to ossify in S. aurata appear to be related with functional requirements, so that structures involved directly in feeding and breathing generally appear and ossify before those that are not. The ontogeny of different regional structures revealed that generally the dermal bones ossify before the cartilage replacement bones. Comparison of S. aurata viscerocranial skeleton ontogeny with that of phylogenetically distant fish demonstrates that different ossification strategies exist in higher and lower teleost fish.